(untitled) (Asian Journal of Medical Research and Health Sciences, 2026)
Background: Children with neurodevelopmental disorders often require long-term care and supervision, placing considerable demands on their caregivers. These demands may affect caregivers’ emotional well-being and contribute to psychological distress and increased caregiver burden. Although caregiver burden has been studied in autism spectrum disorder (ASD) and intellectual developmental disorder (IDD), comparative data remain limited. The present study aimed to assess anxiety, depression, and caregiver burden among caregivers of children with ASD and IDD and compare these variables between the two groups. a cross-sectional analytical study was conducted among 120 caregivers (60 caregivers of children with asd and 60 caregivers of children with idd). participants were assessed for anxiety, depression, and caregiver burden. Results: Caregivers of children with ASD and IDD demonstrated significant levels of anxiety, depression, and caregiver burden. Caregivers of children with ASD showed significantly higher burden, anxiety, and depression scores than caregivers of children with IDD. Conclusion: This study suggests that both ASD and IDD impose substantial caregiving demands; however, caregiver burden, anxiety, and depression were significantly higher among caregivers of children with ASD.